New independent control of a Bi Machine system powered by a multi-leg inverter applied to four in-wheel motor drive electric vehicle - Benkhalfallah Adda; Hartani Kada; Norediene Aouadj; Karim Abdelkader Belhia (Institute of Advanced Engineering and Science, 2023)
The four-wheel-drive electric vehicle's traction chain is powered by four permanent-magnet synchronous motors (PMSM), powered by a single three-phase, five-leg inverter (FLI). In order to achieve the behavior of a mechanical differential and to require the parallel wheel-motors to turn at identical or different speeds, using this structure, an independent control is applied on each driving wheel. For this particular structure, there is a shared inverter leg between the two phases of two machines. The other two phases of each machine are attached to their own two inverter legs. This work's main focus is the suggestion of a new DTC technique for the control of an electric vehicle (EV) with two set bi-PMSM motor-wheels fed in parallel by a single three-phase five-leg inverter. The simulation results show that this new control technique can ensure excellent dynamics of the electric vehicle driving system.